The Tree and the Tree tradition - D, Thamizharasi (International Research Journal of Tamil, 2022)
Literature deals with natural ecological life. People who lived in the Sangam era felt the importance and sweetness of nature. So they lived their life in harmony with nature. Natural resources like water, land, paddy, trees, forests and vines helped the ancient Tamil people to lead a noble life. Ancestors depended on nature to get their sources of life. From the perspective of human life, nature can be seen as a theme, a philosophy that conveys the truth of life, commentary, and allegorical images. In this way, songs in Akananuru are created in harmony with nature. It is especially meant to indicate the prosperity of trees and the livelihood of people associated with trees.